Buddhism: The basics - Cantwell, Cathy (New York Routledge, 2010)
Buddhism: The Basics provides a thorough and accessible introduction to a fascinating religion. Examining the historical development of Buddhism and its presence today, this guide covers principal traditions practices and beliefs ethical guidelines and philosophy religious texts community With helpful features including a detailed map of the Buddhist world, glossary of terms and tips for further study, this is an ideal text for students and interested readers wanting to familiarize themselves with the Buddhist faith.
Keywords: Buddhism